Experimental quantification of electrostatic damage (ESD) in binary reticle with feature of nanometre scale gaps - Razman, Harriman; Awang Md Isa, Azmi; Suaidi, Mohamad Kadim (Wydawnictwo SIGMA-NOT, 2022)
A Binary reticle for lithography circuit patterning is extremerly senstive to electrostatic field. Damaged is seen on its feature after a breakdown voltage occurred between the metal lines. The experimental quantification of ESD for Binary reticle is performed by direct discharge to the feature of Critical Dimension (CD) of 80 nm to 160 nm. Its breakdown voltage correlated to CD but lower than international standard recommendations and observed Electric Field-Induced Migration (EFM) damaged at CD of < 110 nm but ESD for CD > 110 nm to 160 nm.